Analisis Peran Mediasi Harga Terhadap Asosiasi Country Of Origin, Perceived Quality, dan Brand Image Terhadap Keputusan Pembelian - Rosdiana Sijabat (Jurnal Manajemen, 2020)
This article examines perceptions of the country of origin, perceived quality, and brand image of Chinese household appliance products on product purchasing decisions by Indonesian consumers mediated by consumer perceptions of prices. A total of 402 respondents who had purchased home appliances from China filled out questionnaires related to their perceptions of the products studied, and these perceptions were analyzed using PLS-SEM. The analysis results show that perceptions of the country of origin, perceived quality, and brand image have a positive and significant relationship to consumer decisions in buying household brand products from China in Indonesia. Perceptions of price mediate the relationship between country of origin, perceived quality, and brand image on purchasing decisions with positive associations. This study provides new insights into the relationship between country of origin, perceived quality, brand image, and price on product purchasing decisions from China in Indonesia, where both countries are developing countries. The study offers managerial implication on the importance of home appliance manufacturers from China to maintain affordable prices in the Indonesian market.